Radioanalytical Techniques to Quantitatively Assess the Biological Uptake and in Vivo Behavior of Hazardous Substances - Lee, Jae Young; Mushtaq, Sajid; Park, Jung Eun; Shin, Hee Soon; Lee, So Young; Jeon, Jongho (Molecules, 2020)
Concern about environmental exposure to hazardous substances has grown over the past several decades, because these substances have adverse effects on human health. Methods used to monitor the biological uptake of hazardous substances and their spatiotemporal behavior in vivo must be accurate and reliable. Recent advances in radiolabeling chemistry and radioanalytical methodologies have facilitated the quantitative analysis of toxic substances, and whole-body imaging can be achieved using nuclear imaging instruments. Herein, we review recent literature on the radioanalytical methods used to study the biological distribution, changes in the uptake and accumulation of hazardous substances, including industrial chemicals, nanomaterials, and microorganisms. We begin with an overview of the radioisotopes used to prepare radiotracers for in vivo experiments. We then summarize the results of molecular imaging studies involving radiolabeled toxins and their quantitative assessment. We conclude the review with perspectives on the use of radioanalytical methods for future environmental research.
Keywords: Animals; Bacteria; Hazardous Substances; Humans; Nanostructures; Radioisotopes; Technology, Radiologic; Tissue Distribution; Biodistribution; Environmental health; Hazardous substances; In vivo imaging; Radiolabeling